(3GdOYGjI GdSjGSjI hGdKhQGJ GdYQHjI aj YUQ GdaVGA GdQbej(B: (3OQGSGJ JMdjdjI aj bfGJj GdLRjQI hGdj Gf Gf GdCeQjcjI s - (3eMeO GHQGgje(B, (3YHO Gddgs; (3edG(B, (3egOj eMeOs ((3YeGf(B:s (3OGQ ZjOGA ddfTQ hGdJhRjY(B,s, 2018)
(3dbO GSJNOeJ cdeI GdOYGjI aj MVGQGJ GdYGde GdbOje eKdeG hLOJ aj eUQ GdbOjeI hGdYQGb hGdjhfGf hGdQheGf hCeGcf GNQi ,hdcf cOYGjI SjGSjI, aCfgG cGfJ bO HOCJ aj GdbQf GdYTQjf hGdMbjbI Gf GdOYGjI dGjecf Gf jMSH dgG MSGH Gf de jcf gfGc QCj YGe(B.(3dPdc abO GYWjfG GgejI ddQCj GdYGe aj gPG GdHMK, hbO hLOfG Cf GdbQf GdYTQjf YQa HbQf GdQCj GdYGe HSHH JfhY hhaQI hSGFd GdGJUGd GdLeGgjQj hGdOYGjI(B.(3hhLOfG CjVkG Ef GdJfTFI GdGLJeGYjI hGdbje GdOjfjI hGdehGba GdSjGSjI hGdCMOGK GdgGeI hGdbGOI, JYO cKjQI GdCgejI hGdJCKjQ aj Jchjf hJMQjc GdQCj GdYGe(B.(3hGf UGfYj GdOYGjI ZGdHkG eG jSJNOehf WQjbJjjf dfTQ OYGjJge MjK JSJNOe(B:(3CĎ(B-(3GdSjGbGJ GdeYQajI(B. (3H(B- (3GdSjGbGJ GdYGWajI (B. (3aGdOYGjI GdSjGSjI JfLM GPG SGfOJ GdGJLGgGJ GdbGFeI hdcf jUHM ef GdUYH YdjgG Cf JUfY GJLGgGJ eZGjQI deG gh bGFe , hCf GdChVGY GdSjGSjI hGdGbJUGOjI hGdGLJeGYjI hGdMVGQjI hGdCMOGK GdcHQi JYO CcKQ aGYdjI hJCKjQG ef GdOYGjI YfOeG fQjO GdJYGed eY GdQCj GdYGe(B.(3hdbO hLOfG CjVkG Cf GdaQb Hjf GdGYdGe hGdOYGjI jcef aj GdeMJhi hdjS aj GdhSGFd GdGJUGdjI hfSJWjY Gf fdNU Pdc HfbWJjf (B:1- (3aj GdMbGFb (B2- (3aj GdehVhYjI(B- s
(3HjHdjhZQGajG U(B.115 s
Keywords: (3GdOYGjI GdSjGSjI(B: (3GdKhQGJ GdYQHjIs; (3GdOYGjI GdSjGSjI(B: (3GdQCj GdYGes